Effects of urban airborne particulate matter exposure on the human upper respiratory tract microbiome: a systematic review - Sonia Arca-Lafuente; Beatriz Nuñez-Corcuera; Rebeca Ramis; Spyros Karakitsios; Denis Sarigiannis; Saúl García Dos Santos; Amanda Fernández-Rodríguez; Verónica Briz (Respiratory Research)
Abstract Exposure to air pollutants has a direct impact on human health, resulting in increased mortality rates. Airborne particulate matter (PM) has major adverse effects on health and can be classified as high-risk respiratory particles (fine/PM2.5, aerodynamic diameter < 2.5 µm) or thoracic particles (coarse/PM10, aerodynamic diameter < 10 µm). In addition, airborne PM can carry microbial communities that alter the commensal microbiota and lead to dysbiosis. Our aim was to synthesize the current research evidence describing the association between air pollution exposure and the microbiome composition of the upper respiratory tract (URT) of the adult population. In this work, a systematic search of the PubMed, EMBASE and Scopus databases was conducted. A total of 9 studies published from 2018 to 2023 were included. 66.5% of the participants were exposed to PM2.5 concentrations higher than 40 µg/m3, and data showed that PM2.5 atmospheric levels were positively correlated with PM10 (rs = 0.95, p < 0.001). All the reviewed studies performed 16S rRNA sequencing of the V3–V4 region from URT samples, using different methods. Overall, evidence of URT microbiome alterations after high PM exposure was observed, with seasonal and geographical influence. Discordant findings were found about bacterial diversity, with a predominant decrease after exposure to high PM levels. Regarding microbiome composition, the relative abundance of the Actinobacteria phylum declined following exposure to high levels of PM, but that of Bacteroidetes and Fusobacteria increased. The studies showed a low-middle risk of bias due to heterogeneity regarding sample processing, sequencing methods, and confounder control. To confirm the observed evidence of an association between PM levels and alterations in the URT microbiome, we strongly recommend that future research work be conducted in accordance with standard guidelines for reporting microbiome studies. In summary, the entry of fine and coarse particles into the URT is associated with microbial dysbiosis, increasing the risk of developing respiratory diseases and allergies. Prospero registration: This systematic review was registered on PROSPERO (#CRD42023416230) Graphical Abstract